Creative Expressions from the Trans-Atlantic Era: African Women Artistes in Diaspora - OLADEJO Mutiat Titilope (Ученые записки Института Африки Российской академии наук)
The culture of singing and dancing is peculiar to Africa. Before the Trans-Atlantic trade, the culture was a creative expression in everyday life. From a historical perspective, this work examines the movement of African culture into the Trans-Atlantic world through the artistic performances of women in Diaspora. The African Diaspora is a diverse world outside Africa. Hence, this work analyses the experiences across the societies of the African Americans, Afro-Brazilians, the Yoruba Diaspora, Afro-Caribbean, within Africa among others. Women in this spaces have encountered various dynamics of being African descent in al long duree. It examines the historical process that influenced the contemporary practices in the work of female artistes in Diaspora. The work complicates the experiences of female artistes as a manifestation of the characteristics of racial and gender inequalities driven by the struggles for self-worth and determination in the Diaspora. Invariably, this work analysed how cultural ideas from Africa transferred to the diaspora. Significantly, the African female artistes in Diaspora use their work to re-enact and revolve culture by which entrepreneurial tendencies featured. The historical method is adopted.